Particle Swarm Optimization Design of Optical Directional Coupler Based on Power Loss Analysis - Özkan-Bakbak, Pınar (International Journal of Intelligent Systems and Applications in Engineering, 2013)
In this work, feasible design is presented as an optimization problem for an optical directional coupler and designed by using particle swarm optimization (PSO). Principally, identical, weakly guiding, slab and lossless optical waveguides are supposed to be weakly coupled to each other. The power loss and the propagation constant change of TE and TM modes in mutual coupling of two cladded and uncladded optical waveguides are analyzed by the modal analysis and PSO. PSO design of an optical directional coupler is an optimization problem consisting of input variables and design parameters within a fitness function (FF). FF is the power loss of TE and TM modes. PSO should minimize the FF and obtain design criteria. The analysis shows that the results, by using PSO are compatible with modal analysis results. The availability of the optical coupler design by PSO has been tested successfully.